1982
DOI: 10.1079/bjn19820020
|View full text |Cite
|
Sign up to set email alerts
|

The origin of urinary aromatic compounds excreted by ruminants 2. The metabolism of phenolic cinnamic acids to benzoic acid

Abstract: 1. The extent to which phenolic derivatives of benzoic acid (seven); of phenylacetic acid (one); of 3-phenylpropionic acid (one) and of cinnamic acid (six) served as precursors of the urinary benzoic acid excreted by sheep was determined after administration as continuous drips via rumen or abomasal cannulas.2. Phenolic derivatives of benzoic or of phenylacetic acid were not dehydroxylated to yield aromatic acids following administration via either route.3. Rumen infusion of phenolic derivatives of both 3-phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
3

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 34 publications
1
25
0
3
Order By: Relevance
“…1 and 3). As well as human microbiota having the ability to perform these reactions, incubations with rumen microbes gave almost identical results, which were similar to transformations observed in earlier studies (18). For the 5-5 linked dehydrodimer of ferulic acid (Fig.…”
Section: Resultssupporting
confidence: 90%
“…1 and 3). As well as human microbiota having the ability to perform these reactions, incubations with rumen microbes gave almost identical results, which were similar to transformations observed in earlier studies (18). For the 5-5 linked dehydrodimer of ferulic acid (Fig.…”
Section: Resultssupporting
confidence: 90%
“…This fraction probably corresponds to small acid soluble molecules, such as phenolic acids, VFA, oligolignols and phe-bound peptides. It has been observed that released hydroxycinnamic acids (Martin 1982) and phenylalanine (Scott et a1 1964) are transformed in the rumen into soluble phenyl-substituted fatty acids. To estimate the proportion of RAtrans actually resulting from the degradation of lignin into small acid-soluble molecules, we can deduct the radioactivity of the released labelled phenolic acids (6.7% pheCWRRA) and all the labelled proteins (5% pheCWRRA, according to Mosoni et a1 1993) from the radioactivity of the supernatants.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Infusing phenolic acid into the sheep rumen established hydroxycinnamates released from cell walls or from soluble conjugates as the major source of these acids. 18 The alternative origin via the deamination of aromatic amino acids was shown subsequently to account for only a minor proportion of such compounds. 19 The transformation of nonmethoxylated and monomethoxylated hydroxycinnamic acids to 3-phenylpropionic acid is under the control of microbial enzymes and involves the reduction of the side-chain, demethylation of C 3 ferulic and sinapic acids and dehydroxylation (Fig 1).…”
Section: Ruminantsmentioning
confidence: 99%